Electric Field Enlarges Raindrops Beneath Electrified Clouds: Observational Evidence. Issue 14 (22nd July 2021) - Mudiar, Dipjyoti; Pawar, S. D.; Gopalakrishnan, V.; Williams, Earle
Abstract: Simultaneous measurements of cloud electric field and raindrop size at the Earth's surface have been analyzed to investigate an anticipated relation between the two cloud parameters. A significant positive correlation is observed between the magnitude of the surface electric field and raindrop size supported by a theoretical framework advanced here. It is shown that in the presence of an electric field, raindrops increase their size through electrically induced collision and coalescence processes near the Earth's surface. This study also demonstrates that the presence of an electric field inside the cloud can enhance the rain intensity by influencing the growth rate of raindrops. This new insight may be useful for a proper understanding of the rain microphysics and for developing better numerical weather models for simulation and forecasting of heavy rainfall events associated with stronger in‐cloud electrical environments. Plain Language Summary: The rainfall observed at the Earth's surface is a manifestation of different cloud microphysical processes. The condensation of water vapor on cloud condensation nuclei (CCN) and subsequent collision/coalescence between cloud droplets are the two dominant processes of rain formation in the warm phase of cloud. Many laboratory investigations suggest that both processes are quite sensitive to the electrification of the cloud. But direct evidence of the influence of cloud electric field on the rain formation in the real atmospheric condition is lacking till now. With simultaneous observations of the cloud electric field and the raindrop size distribution below a few strongly electrified clouds, for the first time, it has been shown that larger cloud electric field remains associated with larger raindrops at the Earth's surface. A mathematical framework has also been developed to support the observations. It has also been shown that the cloud electric field can modify the rain rate at the Earth's surface by enhancing the growth of raindrops. Key Points: Simultaneous measurements of surface electric field, raindrop size and rain rate have been analyzed The results indicate that the electric field below strongly electrified cloud can enhance the size of raindrops and hence the rain rate These results may be useful for better understanding and prediction of heavy rainfall events associated with stronger electrification